KEPUASAN PENGGUNA LULUSAN PADA MAHASISWA D3 MICE UNIVERSITAS TRISAKTI - Aekram Faisal; Yudhaputri, Egabetha A (Media Riset Bisnis & Manajemen, 2024)
This study aims to analyze the satisfaction level of users of graduates from the Event Management (MICE & Event Management) Program at the Faculty of Economics and Business, Universitas Trisakti, which includes an evaluation of the graduates' soft skills and hard skills. The evaluated aspects include integrity, professionalism, English proficiency, information technology skills, communication, teamwork, and self-development for soft skills, as well as tax management, auditing, corporate reporting, and strategic management for hard skills. The results of the study show that the satisfaction level of users of graduates from the MICE & Event Management Program in the Odd Semester 2021/2022 period is Excellent, with the majority of respondents expressing high satisfaction with the graduates' performance. Although the evaluation results show excellent performance, this study also identifies the need for further evaluation to maintain and enhance the quality of graduates in the future. The study suggests expanding the number of respondents and involving a broader range of stakeholders to gain a more comprehensive understanding of the effectiveness of the education provided by this program